A Phaseolus vulgaris Extract Reduces Cue-Induced Reinstatement of Chocolate Seeking in Rats - Lorrai, Irene; Piga, Valentina; Carai, Mauro A. M.; Riva, Antonella; Morazzoni, Paolo; Gessa, Gian Luigi; Colombo, Giancarlo; Maccioni, Paola (Frontiers in Pharmacology, 2016)
Previous evidence has suggested that treatment with a standardized dry extract of Phaseolus vulgaris reduced intake and operant self-administration of highly palatable foods and fluids in rats and mice. The present study was designed to assess whether such extract was also effective in reducing seeking behavior for a highly hedonic chocolate-flavored beverage, using a “reinstatement” procedure adopted from the drug addiction research field and modeling relapse behavior. Rats were initially trained to lever-respond for the chocolate-flavored beverage under the Fixed Ratio (FR) 10 (FR10) schedule of reinforcement. Subsequently, rats were exposed to an extinction responding phase, during which lever-responding – being unreinforced – diminished progressively up to extinction. Lever-responding was then powerfully reinstated by the non-contingent presentation of a complex of gustatory, olfactory, auditory, and visual stimuli previously associated to the availability of the chocolate-flavored beverage. Acute, intragastric administration of P. vulgaris dry extract (100 and 500 mg/kg) reduced lever-responding by 40-45%, in comparison to vehicle condition. These results indicate the ability of P. vulgaris dry extract to reduce seeking behavior for a highly palatable nourishment in an experimental model of relapse into disordered eating of palatable foods. The unavailability of the chocolate-flavored beverage in the reinstatement session tends to exclude that the observed effect of the P. vulgaris dry extract was secondary to any inhibition of carbohydrate metabolism; conversely, it is the likely consequence on a central action on the rewarding and hedonic properties of food.